Non-fatal suicidal behaviour and burnout among veterinarians in Valparaíso, Chile - Weinborn, Romy (2023)
The veterinary medicine profession has a suicide rate 3 to 4 times higher than that of the general population, where 17% of veterinary doctors have had suicidal ideation. The aim of this work was to describe the relationship between job stress and the prevalence of suicidality (non-lethal suicidal behavior) in Chilean veterinary doctors practicing in the Valparaíso region, Chile. During 2019-2021, using the Google platform, the sociodemographic questionnaires, SAD PERSONS, Columbia Suicide Severity Rating Scale and the Maslach Burnout Inventory (MBI) were carried out. In total, 102 valid surveys were received. A prevalence of 23.5% of individuals with burnout and 63.7% of subjects at risk (low, medium, high) was found in both suicide risk scales. Furthermore, it is possible to show that subjects who present alterations in the emotional exhaustion subscale (MBI) have greater suicidal tendencies. This shows the importance of preventing factors linked to work stress, since they would be linked to suicidality in this population.